Updates on the Neoserica vulpes group (Coleoptera, Scarabaeidae, Melolonthinae, Sericini): new species and records - Ahrens, Dirk (European Journal of Taxonomy, 2023)
Here, I describe four new species of the Neoserica vulpes species group: Neoserica daxue sp. nov., N. mianningana sp. nov., N. myanmarensis sp. nov., and N. yanyuan sp. nov. Genitalia and habitus of the new species are illustrated. Additional records of species from the group are given and the key to species of the Neoserica vulpes species group is updated.